Digest: A synergistic approach explains the evolutionary connection between brain size and longevity. (1st December 2020) - Silva, Willian T.A.F.
Abstract: The cognitive buffer hypothesis poses that brain size evolves to buffer individuals from environmental changes, increasing survival. Jiménez‐Ortega et al. (2020) explored this hypothesis using a phylogenetic path analysis and showed that there is a direct causal link between brain size and longevity in birds, even when allometric effects are taken into account. Furthermore, a synergistic model was better supported than models that included independent effects of brain size and body size.